Indicators of attacking actions of various duration of highly qualified handballtTeams in conditions of numerical inequality - Melnyk, V. O.; Kudrina, N. V. (Ukrainian Journal of Medicine, Biology and Sport, 2020)
The main factor in achieving sustainable sports results in the concept of training is the constant improvement of training technology, which is manifested in bringing the training of highly qualified handball players to the level of permanent readiness for competitive activities. The purpose of the study was to identify the features of offensive actions of different duration of highly qualified handball teams in terms of numerical inequality. Material and methods. The analysis of literature sources was carried out in order to form the purpose and determine the main directions of the research. Pedagogical observation was conducted in order to determine the quantitative indicators of the offensive actions of highly qualified handball teams in terms of numerical inequality and their effectiveness. Methods of mathematical statistics were used to determine the effectiveness of offensive actions of handball teams in terms of numerical inequality and to determine significant differences between the defined indicators. Results and discussion. Analysis of the results suggests that the quantitative indicators of offensive actions in numerical inequality are determined primarily by the efforts of teams to maximize the numerical advantage in the majority and the desire of teams in the numerical minority not to allow their opponents to do such actions. Statistical verification showed that differences between the effectiveness of offensive actions of highly qualified handball teams of different duration were almost never recorded (p> 0.05). Only the effectiveness of offensive actions lasting 1-10 seconds differed significantly from the effectiveness of offensive actions lasting 11-20 seconds (p <0.05). Statistical verification of differences between the indicators of the effectiveness of offensive actions of highly qualified teams in the numerical minority showed the following: the effectiveness and efficiency of attacks in the numerical minority lasting 1-10 seconds differed significantly from similar indicators of attacks lasting 11-20 seconds and> 50 seconds (p <0.05 ). It was also found that the indicators of effectiveness and efficiency of attacks lasting> 50 seconds significantly differed from the indicators of attacks lasting 31-40 seconds and 41-50 seconds (p <0.05). As to other data, no significant differences were found. Conclusion. The largest quantitative indicators of the performance of offensive actions in the numerical majority were recorded during the execution of attacks lasting 11-20 seconds, due to the advantage in the number of players. In numerical minorities, highly qualified teams carried out the most attacks lasting 31-40, 41-50 and> 50 seconds. This can be explained by the attempt to maximize the time of removal of the player. Quantitative indicators of the implementation of offensive actions of different duration of highly qualified handball teams are directly to the quantitative execution of offensive actions. The highest efficiency of realization of game moments was recorded during attacks lasting 1-10 seconds both in the numerical majority and in the numerical minority. This is explained by the completion of attacking actions at close range. Low efficiency of attacking actions lasting > 50 seconds was caused by effective actions of defenders and restriction of preparatory actions owing to the warning about passive conducting of game.